PEMISAHAN DAN ANALISIS CESIUM DALAM PEB U3Si2/Al TMU 2,96 gU/cm3 PASCA IRADIASI DENGAN METODE PENGENDAPAN CHLOROPLATINATE - Nugroho, Arif; Boybul, Boybul; Indaryati, Sutri; Haryati, Iis; Kriswarini, Rosika; Ginting, Aslina Br. (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Fuel burnup is an important parameter for determining the quality and integrity of irradiated nuclear fuel. The most important parameters in the calculation of burnup is the separation process and 137Cs content analysis sampled from the irradiated plate fuel. This research has conducted separation and analysis of the 137Cs contained in irradiated U3Si2/Al plate by chloroplatinate precipitation method. This method requires that the sample has to be made free from elements that may interfere with the precipitation process. The separation is done by precipitation of 137Cs isotope in the form of Cs2PtCl6. The precipitation process uses CsNO3 as non-active carrier with varied weight of 0.0263; 0.0501; 0.0754; 0.1036 ; 0.2064; 0.3020, and 0.4017 g. The CsNO3 carrier is added in order to obtain more ammount of precipitate of Cs in the form of Cs2PtCl6 because CsNO3 has similar chemical properties with 137Cs in uranyl nitrate solution. The 137Cs isotope is coprecipitated in Cs2PtCl6, and γ-spectrometry is used in the determination of the content of 137Cs in Cs2PtCl6 precipitate. The separation results show that addition of 0,1036 g CsNO3 has recovered 0.000328 g/g-sample of 137Cs from 0.000465 g/g-sample in irradiated U3Si2/Al solution, or a recovery of 70.4753%. Recovery value by this method is still lower when compared to other 137Cs separation methods due to longer steps of separation process, which may cause many errors in the sample preparation process.